The Essence And Stages Of Development Of The "Green" Economy Concept (Eurasian Journal of History, Geography and Economics, 2024)
This article shows the essence of the green economy concept, the stages of sustainable development, and the main task of the "Green" economy is to change production and consumption processes in accordance with ecological standards